Inflationary repercussions the shift in cost management and pricing strategies of coffee shop businesses in Iloilo City - Lencioco, Steven lester B.; Misajon, Bless andre G.; Pregil, Shaznie Aisel L.; Talaman, Keassel Faye O.; Tionko, Lance Nicoudemus D. (2022)
The immense growth of cafe establishments and coffee shop goers were evident despite the economic crisis faced by the business during the pandemic. External factors left the coffee shops as no exception to the effects of inflation. This led to the conduct of this qualitative study aiming to centralize on the repercussions of price hikes to the cost management and pricing strategies of the coffee shops situated in Iloilo City, the center of trade and commerce and a highly urbanized metropolis. Specifically, this study sought to determine the cost management practices adopted and pricing strategies implemented by the businesses in response to inflation as well as the impacts of these on the stakeholders. Data were directly collected from the proprietors of the coffee shops and supported by review literature ; thereafter, thematic analysis was utilized to critically analyze the responses gathered. As MSMEs, the respondents acknowledged that cost management and pricing strategies are important for the survival of the business. As the economy struggles due to the pandemic and the resulting inflationary effects it brought to the market, the respondents made adjustments to their cost management the pricing strategies, however, remain constant as the respondents continue to employ the same strategies and only the amount of mark-up is adjusted, considering the need to maintain their margin. The study recommends entering futures contracts, implementing economic order quantity (EOQ) model, solidifying product positioning, adopting an automated accounting system, establishing a system-wide crisis management plan, usage of enhanced budgeting and forecasting techniques, creating a platform for MSMEs to easily access supplementary funds for expansion, and establishment of a Public Supply Hub exclusive for MSMEs.
[Research Paper] (B.A. 199.2-Business Research II). -- [Iloilo City : University of the Philippines, College of Management], June 13, 2023.